Exploring Consumers' Acceptance of E-Marketplace Using Tam and Flow Theory - Agung Purwanto; Nurahman; Andy Ismail (Universitas Djuanda, 2020)
Abstract: One business models of E-commerce which well-developed is E-Marketplace. The internal competition of E-Marketplace remains tough yet some achieve its successful compared to the others. The parameter of successful E-Marketplace can be seen by the numbers of acceptance by the costumers. Hence, this research on E-marketplace acceptance is significant to be done. This research takes a case study in one of the Indonesian markets, named the ‘Pusat Perbelanjaan Mentaya’ (PPM) regarding the use of the E-marketplace. This research aims to find out the adoption of e-marketplace acceptance. Our research model based on Technology Acceptance Model (TAM) which is modified by adding shopping enjoyment variable (Flow Theory). This research applies quantitative research method; spreading questionaries and surveys. The data obtained were 240 from the PPM consumers who use E-marketplace application. Then the data would be used to examine the relationship between the variables of the proposed model. The results of this study show that the perception of the use of E-Marketplace application effects the perceived benefits. This due to the ease of operating the E-marketplace service affects users, moreover, sales and purchase transactions become more effective and efficient. In essence, the ease perceived also has an influence of the users’ attitude. This shows that E-marketplace service users feel that using these services increases effectiveness and benefits; they will not refuse to use E-marketplace services. The results in this study that the variable attitude towards use of Behavioral Intention is not accepted. Technology Acceptance Model, Technology Acceptance Theory, Shopping enjoyment, E-marketplace